Analysis of the Implementation of Standard Precautions in Preventing Healthcare Associated Infections (HAI's) at Wampu Norita General Hospital - Sitanggang, Loym Ristumerry; Kasim, Felix; Sirait, Reni Aprinawaty (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Standard precautions are needed to implement the IPC program in hospitals. Implementation of Standard Precautions can be carried out because it is driven by the PPI Committee or Team. The PPI Committee or Team is formed based on needs, workload, and type of health service facilities. The eleven components of standard precautions can be implemented in every health service, especially in Indonesia which is trying to reduce HAIs. HAIs are known as nosocomial infections that occur in hospital patients, where infection has not occurred while the patient has been hospitalized for more than 48 hours. The large risk of infection in hospitals encourages the need to reduce the risk of infection through the PPI Program. A descriptive qualitative research method was chosen to obtain meaning from a number of individuals and social groups. The qualitative research process includes asking questions, collecting data, analyzing data, and interpreting the meaning of the data. The sample in this study was 8 informants, including Hospital Leaders, heads of Hospital Quality, Nurses in charge of the field, Daily Executive Officers, and Executive Nurses in service units. The results show that the PPI policy has been implemented well which includes the PPI Structure and Team, Infection Surveillance Manual, Standard Precautions and implementation of Hand Hygiene and PPE, as well as the budget. Meanwhile, the condition of facilities and infrastructure is not optimal, such as hand hygiene facilities and use of PPE, collection of HAI infection surveillance data, and training. Conclusion: The Standard Precautions Implementation Policy already exists and is based on Minister of Health Regulation No. 27 of 2017. The results of the Hand Hygiene and PPE compliance audit do not match the Quality Profile, facilities, and infrastructure are not optimal, namely below 100%, and stock in the premises is still limited